Using Inexpensive Technology and Multimedia to Improve Science Education in Rural Communities of Nepal - Neupane, Sujaya (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
This article explores an ongoing project that promotes science education in rural communities of western Nepal by using affordable technology. With the advent of inexpensive technology and multimedia resources, teaching materials for science education can be accessed with a much smaller budget than was previously possible. A preliminary survey done in two schools of Baglung district in Nepal found a significant lack of funding for science education. Using affordable computing technology such as Raspberry Pi and open-source electronic library contents, including those provided by Khan Academy and Wikipedia, this project will help foster the currently underutilized talent that exists in the country by making communities less dependent on external educational aid and hence promote ownership and progress of online educational platforms.